2016
DOI: 10.1515/ijamh-2016-0033
|View full text |Cite
|
Sign up to set email alerts
|

Is vaping a gateway to smoking: a review of the longitudinal studies

Abstract: This review highlights the strong evidence that not only are ECs are not an effective tool for smoking cessation among adolescents, they actually are associated with higher incidence of combustible cigarette smoking. Policy makers need to recognize of the insidious nature of this campaign by the tobacco industry and design policies to regulate it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 44 publications
1
54
0
3
Order By: Relevance
“…Notably, there was substantial variabililty in documented ENDS use across departments and less than half of ENDS documentation occurred in pediatrics among patients aged 12–17. Given emerging evidence that ENDS use may serve as a gateway to tobacco smoking among youth (Chatterjee et al, 2016), routine documentation in pediatrics, in particular, would allow for a more thorough assessment of the longitudinal impact of ENDS use on changes in smoking status and health.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there was substantial variabililty in documented ENDS use across departments and less than half of ENDS documentation occurred in pediatrics among patients aged 12–17. Given emerging evidence that ENDS use may serve as a gateway to tobacco smoking among youth (Chatterjee et al, 2016), routine documentation in pediatrics, in particular, would allow for a more thorough assessment of the longitudinal impact of ENDS use on changes in smoking status and health.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the longitudinal effects of e-cigarette use on onset of smoking among adolescents and young adults concluded that e-cigarette use does lead to a higher incidence of combustible cigarette smoking [50]. …”
Section: E-cigarettes and Childrenmentioning
confidence: 99%
“…E-cigarettes are more popular among younger individuals, who are also more likely to believe that they are less harmful than cigarettes in the United Kingdom, but the patterns and pathways of use among adolescents remain unclear [1][2][3] . A key question in the debate is whether experimentation and use among adolescents is a gateway to smoking tobacco 4,5 . While multiple studies have shown that regular use of e-cigarettes and, to some extent, experimentation with the product are rare among non-smokers, the cross-sectional nature of these studies precludes conclusions with regards to transition from e-cigarettes to combustible tobacco and vice versa 1,6 .…”
Section: Introductionmentioning
confidence: 99%